Rezension von: Ehrhart, Otto, J. H. Dominik, Jagdherr von Waldpeuren - Rühle, Oskar (Schwäbische Heimat, 1959)
Otto Ehrhart, Der Jagdherr von Waldpeuren, 220 Seiten, DM 8.50. Maximilian Dietrich Verlag, Memmingen.